POY version 5: phylogenetic analysis using dynamic homologies under multiple optimality criteria. (13th June 2014) - Wheeler, Ward C.; Lucaroni, Nicholas; Hong, Lin; Crowley, Louise M.; Varón, Andrés
Abstract We present POY version 5, an open source program for the phylogenetic analysis of diverse data types including qualitative, aligned sequences, unaligned sequences, genomic data, and user‐defined sequences. In addition to the maximum‐parsimony optimality criterion supported by POY4, POY5 supports several types of maximum likelihood as well as posterior probability. To make these analyses feasible, new heuristic search algorithms and parallelization options have been implemented for all criteria.